PEMAKNAAN KECANTIKAN PEREMPUAN PADA GROUP CHAT LINE ALUMNI SEKOLAH BERBASIS PESANTREN INSAN CENDEKIA GORONTALO - Utami Putri, Rizky; Dwiningtyas Sulistyani, Hapsari (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2019)
Islamic boarding schools are schools that base their education on the teachings of Islam. The beauty of Muslim women related to face, body, and appearance in a boarding school-based school community is interpreted based on religious texts adhered to. This study aims to see how the pesantren-based school community constructs the meaning of female beauty and how it is constructed through a group conversation on media such as LINE. This research is ethnomethodology research which is studied using qualitative methods with Conversational Analysis. The theory used in this study refers to the Beauty Myth by Naomi Wolf. The results of the study found that women's beauty was interpreted based on Islamic texts, namely beautiful without excessive makeup and beautifully dressed in Shari'a. The arrangement of conversations that refer to turn-taking is done in sequence (sequence) shows that the meaning of beauty is controlled by male participants, while female participants tend to be a back channel. The Repair Organization and The Organization of Turn-design show the use of language signs and symbolization that affirms the meaning of beauty which leads to beautiful meaning without excessive makeup and beautifully dressed in Shari'a. The meaning of beauty in the conversation of the alumni group of Islamic boarding school Insan Cendekia Gorontalo is a form of Beauty Myth. LINE as an online media is considered capable of perpetuating the beauty myth that appears in conversations.